'Low‐normal' motor skills in infants at high risk for poor developmental outcomes: A prevalence and prognostic study. (21st May 2022) - Danks, Marcella; Flynn, Emma J.; Gray, Peter H.; Hurrion, Elizabeth M.
Abstract: Aim: To investigate the prevalence and prognostic value of 'low‐normal' motor skills in infants at high‐risk for poor developmental outcomes. Method: Infants born extremely low‐birthweight and extremely preterm discharged from neonatal intensive care between 2015 and 2018 completed the Alberta Infant Motor Scale (AIMS), Neuro‐Sensory Motor Developmental Assessment (NSMDA) at corrected age 4, 8, and 12 months, and Griffiths Mental Development Scale at corrected age 12 months. Results: Participating infants ( n  = 191) with a mean gestational age (95% confidence interval [CI]) of 26.80 weeks (26.60, 27.1) and mean birthweight (95% CI) of 869 grams (843, 895) included 45 (23.80%) infants small for gestational age. AIMS rated 50.32%, 35.37%, and 14.86% of infants within the 'low‐normal' motor skills range (1–2 SD below the mean for age) at 4, 8, and 12 months respectively. Of the infants within the AIMS 'low‐normal' skills range, 55.70%, 88.46%, and 59.10% were classified as having impairment by NSMDA at 4, 8, and 12 months respectively. Griffiths assessment at 12 months identified only 7.33% of infants with 'low‐normal' skills and 3.33% with motor disability. Minimal motor impairment rating on the NSMDA at 4 or 8 months significantly predicted general development at 12 months. Interpretation: High‐risk infants with 'low‐normal' motor skills may warrant referral to early intervention as associated impairment represents increased risk for poorer general development outcomes. What this paper adds: High prevalence of 'low‐normal' motor skill exists in high‐risk infants. Clinical motor assessment validly identifies infants with motor impairment. Minimal motor impairment in high‐risk infants is prognostic of general development. High‐risk infants with 'low‐normal' motor skills may warrant early intervention. Griffiths Scales of Child Development, Third Edition assessment at 12‐months age may under‐identify motor difficulties. What this paper adds: High prevalence of 'low‐normal' motor skill exists in high‐risk infants. Clinical motor assessment validly identifies infants with motor impairment. Minimal motor impairment in high‐risk infants is prognostic of general development. High‐risk infants with 'low‐normal' motor skills may warrant early intervention. Griffiths Scales of Child Development, Third Edition assessment at 12‐months age may under‐identify motor difficulties. Of the infants within the 'low‐normal' skills range (1–2 SD below mean for age), 55.70%, 88.46%, and 59.10% were classified as having impairment at 4, 8, and 12 months corrected age. Minimal motor impairment rating on the NSMDA at 4 or 8 months significantly predicted poorer Griffith's General quotient at 12 months. This original article is commented on by Kerem Günel on pages 1439–1440 of this issue. This article's abstract has been translated into Spanish and Portuguese. Follow the links from the abstract to view the translations. ResumenHabilidades motoras 'normales‐bajas' en bebés con alto riesgo de trastornos del desarrollo: un estudio de prevalencia y pronóstico: Objetivo: Investigar la prevalencia y el valor pronóstico de las habilidades motoras "normales bajas" en bebés con alto riesgo de trastornos del desarrollo. Método: Los bebés nacidos con un peso extremadamente bajo al nacer y extremadamente prematuros dados de alta de la unidad de cuidados intensivos neonatales entre 2015 y 2018 completaron la Escala motora infantil de Alberta (AIMS), Evaluación del desarrollo motor neurosensorial (NSMDA) a la edad corregida de 4, 8 y 12 meses. y la Escala de Desarrollo Mental de Griffiths a la edad corregida de 12 meses. Resultados: Los lactantes participantes (n = 191) con una edad gestacional media (intervalo de confianza [IC] del 95 %) de 26, 80 semanas (26, 60, 27, 1) y un peso al nacer medio (IC del 95 %) de 869 gramos (843, 895) incluyeron 45 (23, 80 %) lactantes pequeños para la edad gestacional. La AIMS calificó al 50, 32 %, 35, 37 % y 14, 86 % de los bebés dentro del rango de habilidades motoras "normal‐baja" (1‐2 DE por debajo de la media para la edad) a los 4, 8 y 12 meses, respectivamente. De los bebés dentro del rango de habilidades 'bajo‐normal' de AIMS, el 55, 70 %, el 88, 46 % y el 59, 10 % fueron clasificados como afectados por la NSMDA a los 4, 8 y 12 meses, respectivamente. La evaluación de Griffiths a los 12 meses identificó solo el 7, 33 % de los bebés con habilidades "normales bajas" y el 3, 33 % con discapacidad motora. La calificación de deterioro motor mínimo en la NSMDA a los 4 u 8 meses predijo significativamente el desarrollo general a los 12 meses. Interpretación: Los bebés de alto riesgo con habilidades motoras "normales‐bajas" pueden justificar la derivación a una intervención temprana, ya que el deterioro asociado representa un mayor riesgo de trastornos del desarrollo general más deficientes. Resumo: Habilidades motoras "abaixo‐do‐normal" em bebês com alto risco para um pobre desenvolvimento: um estudo de prevalência e prognóstico: Objetivo: Investigar a prevalência e o valor prognóstico de habilidades motoras "abaixo‐do‐normal" em bebês de alto risco para pobre desenvolvimento. Método: Bebês nascidos de extremo baixo peso ao nascer e extremamente prematuros que receberam alta da terapia intensiva neonatal entre 2015 e 2018 e completaram a Alberta Infant Motor Scale (AIMS), Neuro‐Sensory Motor Developmental Assessment (NSMDA) na idade corrigida de 4, 8 e 12 meses, e Griffiths Mental Development Scale aos 12 meses de idade corrigida. Resultados: Participaram 191 bebês com idade gestacional média (intervalo de confiança de 95% [IC]) de 26, 80 semanas (26, 60; 27, 1) e peso médio ao nascer (IC 95%) de 869 gramas (843, 895), dentre estes 45 (23, 80%) lactentes eram pequenos para a idade gestacional. A AIMS pontuou 50, 32%, 35, 37% e 14, 86% dos bebês dentro da faixa de habilidades motoras "abaixo‐do‐normal" (1‐2 DP abaixo da média para a idade) aos 4, 8 e 12 meses, respectivamente. Dos bebês dentro da faixa de habilidades "abaixo‐do‐normal" da AIMS, 55, 70%, 88, 46% e 59, 10% foram classificados como tendo prejuízo pelo NSMDA aos 4, 8 e 12 meses, respectivamente. A avaliação de Griffiths aos 12 meses identificou apenas 7, 33% dos bebês com habilidades "abaixo‐do‐normal" e 3, 33% com deficiência motora. A classificação de disfunção motora mínima no NSMDA em 4 ou 8 meses previu significativamente o desenvolvimento geral em 12 meses. Interpretação: Bebês de alto risco com habilidades motoras "abaixo‐do‐normal" podem justificar o encaminhamento para intervenção precoce, pois o comprometimento associado representa um risco aumentado para desfechos pobres no desenvolvimento geral.